Adoption of social media in The Creative MSMEs Sector Through a Bibliometric Approach - Zahril Maulana Jilham Al'ula; Lissa Rosdiana Noer (Jurnal Indonesia Sosial Teknologi, 2024)
In today's digital era, the adoption of social media by creative micro, small, and medium enterprises (MSMEs) is increasingly essential for marketing strategies and customer engagement. This research aims to investigate social media adoption among creative MSMEs, identify existing trends, and analyze factors influencing platform use. Through a bibliometric analysis approach, the study examines relevant literature to gain insights into the dynamics of social media adoption in the context of creative MSMEs. The findings reveal a significant rise in publications on MSMEs and social media, particularly since 2008, indicating a growing recognition of social media's role in marketing strategies. Key factors influencing adoption include MSME owners' knowledge and skills, managerial support, and resource availability. Although challenges like technical skill limitations and costs remain, social media’s potential to enhance customer engagement and loyalty highlights the need for greater attention. This study concludes by underscoring the importance of additional support, such as training and resources for MSMEs, and suggests further research to explore social media adoption longitudinally and examine the impact of cultural factors.